Electromigration-enhanced atomic diffusion to improve coating interface bonding. (September 2021) - Huang, Xiaoshan; Yan, Longge; Zhang, Xinfang
Abstract: The chromium-coated zirconium alloy has a conflicting problem that the diffusion layer that enhances the interface bonding force cannot be formed due to the slow diffusion of interface atoms at low temperature, and the performance of the substrate is deteriorated at high temperatures. In this study, the pulsed electric current was used to form the interface diffusion layer at low temperature driven by electromigration, and the processing temperature was lower than the conventional method by more than 300 °C. Electropulsing can significantly increase the diffusion coefficient of interface atoms and reduce the activation energy, from 139.61 kJ/mol to 80.17 kJ/mol. In addition, the current density gradient existing between the coating and the substrate is calculated, and the driving force for its formation plays a vital role, which can be coupled with the chemical potential gradient to enhance the diffusion of atoms at the interface. Graphical Abstract: Image, graphical abstract